BILATERAL NEPHROBLASTOMATOSIS: A ROLE FOR MULTISLICE CT - SRINAKARIN, Jiraporn; AREEMIT, Suchart; KULARBKAEW, Churairat; CHAMADOL, Nittaya; JIRAVUTTIPONG, Apichart; WIANGNON, Surapon (The ASEAN Journal of Radiology, 2023)
Nephroblastomatosis is an abnormality of nephrogenesis characterized by incomplete maturation of the primitive nephrogenic cells. We report on one case of bilateral nephroblastomatosis in an 11-month-old boy who had an abdominal mass on the left side for 8 months. The boy had no other physical anomalies; he appeared healthy and had good development. A sonogram and an intravenous urogram revealed diffuse enlargement of both kidneys and ill-defined hyperechoic lesions covering both kidneys, except the lower pole of the right kidney. A multislice CT scan, performed with and without contrast medium, took no more than 10 minutes. We observed extensive enlargement of both kidneys and multiple solid masses throughout the left kidney and the upper half of the right kidney. Reconstruction on multi-planar views of both renal masses gave as good or better than MRI for displaying the extension of renal masses and renal vascular status. Surgical and pathologic findings are discussed in more detail.